Radezolid Is More Effective Than Linezolid Against Planktonic Cells and Inhibits Enterococcus faecalis Biofilm Formation - Zheng, Jinxin; Chen, Zhong; Lin, Zhiwei; Sun, Xiang; Bai, Bing; Xu, Guangjian; Chen, Junwen; Yu, Zhijian; Qu, Di (Frontiers in Microbiology, 2020)
The aim of this study was to compare the effects of radezolid and linezolid on planktonic and biofilm cells of Enterococcus faecalis. A total of 302 E. faecalis clinical isolates were collected, and the minimum inhibitory concentrations (MICs) of radezolid and linezolid were determined by the agar dilution method. Changes in the transcriptome of a high-level, in vitro-induced linezolid-resistant isolate were assessed by RNA sequencing and RT-qPCR, and the roles of efflux pump-related genes were confirmed by overexpression analysis. Biofilm biomass was evaluated by crystal violet staining and the adherent cells in the biofilms were quantified according to CFU numbers. The MIC50/MIC90 values of radezolid (0.25/0.50 mg/L) against the 302 E. faecalis clinical isolates were eightfold lower than those of linezolid (2/4 mg/L). The radezolid MICs against the high-level linezolid-resistant isolates (linezolid MICs ≥64 mg/L) increased to ≥4 mg/L with mutations in the four copies of the V domain of the 23S rRNA gene. The mRNA expression level of OG1RF_12220 (mdlB2, multidrug ABC superfamily ATP-binding cassette transporter) increased in the high-level linezolid-resistant isolates, and radezolid and linezolid MICs against the linezolid-sensitive isolate increased with overexpression of OG1RF_12220. Radezolid (at 1/4× or 1/8× the MIC) inhibited E. faecalis biofilm formation to a greater extent than linezolid, which was primarily achieved through the inhibition of ahrC, esp, relA, and relQ transcription in E. faecalis. In conclusion, radezolid is more effective than linezolid against planktonic E. faecalis cells and inhibits biofilm formation by this bacterium.